Osteogenic stem-cell characterization and development: potentials for cytotherapy. - Triffitt, J; Oreffo, R; Virdi, A; Xia, Z (2001)
BACKGROUND: Primitive progenitors of bone tissue exist postnatally and exhibit stem-cell characteristics, as shown by extensive renewal potential, and capacity to differentiate into all characteristic connective tissue types, including bone, cartilage, fat, fibrous tissue, muscle and hemopoietic stroma. METHODS: A wide variety of investigative techniques have been applied to characterize and assess differentiation of the normally non-cycling osteogenic stem cells. These include methods to assess in vitro and in vivo differentiation potentials, the production and use of Abs to identify surface markers, the expression of specific genes and, more recently, incorporation of marker genes (beta-galactosidase, green fluorescent protein) to study cell fate after implantation at tissue sites. RESULTS: Some antigenic cell-surface molecules reactive with MAbs generated by a number of laboratories have been identified. For cell-fate studies, retroviral insertion of beta-galactosidase or green fluorescent protein genes into human marrow stromal progenitors has been accomplished with high efficiency. The stromal cell phenotype and cellular functions in vitro are not significantly altered by these genetic modifications. In vivo transplantation in immunodeficient animals demonstrates migration and persistence of marrow stromal cells to skeletal and other tissue sites. DISCUSSION: None of the Abs generated against surface markers of early progenitors are absolutely lineage and cell-stage specific, but the respective Ags appear to participate in cell adhesion and cell-signalling mechanisms. These may be important in stem-cell activation and subsequent early osteogenic development. Studies of cell fate indicate feasibility for future uses in therapy of bone deficiency diseases and the potential for development of gene therapy procedures in these and other conditions.